DEVELOPMENT OF THE SUSTAINABLE ENTREPRENEURSHIP MODEL (Malaysian Management Journal, 2020)
The most prominent feature of today’s economy is rapid change. To succeed in such an economy, countries must be able to adapt to these changes with great agility. One of the most potent tools for achieving this end is sustainable entrepreneurship. Sustainable entrepreneurs are those who undertake entrepreneurial endeavors while taking into account different aspects of social, economic and environmental sustainability. These entrepreneurs strive to keep their resources focused on sustainable development and to balance the objectives of entrepreneurial success and sustainability so as to solve social and environmental problems. In this study, after reviewing the research literature and identifying the factors pertinent to sustainable entrepreneurship, a conceptual model was developed by drawing on the expertise of 10 experts, who were selected by snowball sampling. Interpretive Structural Modeling (ISM) approach was used to examine the network of relationships among the factors. The findings showed that the considered factors fall into four levels: sustainability culture was placed at the most fundamental level, legal requirements, resource preservation, social participation, green management and human resources management were placed at the second level, social justice, effective and efficient processes, and customer-centricity were placed at the third level, and social well-being and economic benefits were identified as the top-level factors or outputs of sustainable entrepreneurship. The proposed model depicted means, process, first order and ultimate goal in inhacing entrepreneurship sustainability endeavors.